Subacute sclerosing panencephalitis: case based review - Singh, Raman; Mahajan, Zubin A.; Mehta, Sameera R.; Ranchhod, Jayesh; Nadkarni, Soham J. (International Journal of Research in Medical Sciences, 2020)
Subacute sclerosing panencephalitis (SSPE) is a chronic debilitating condition that occurs in children affected with measles. SSPE is broadly distinguished as typical SSPE, the more rampant form, occurring over a period of years following primary measles infection, while the atypical has a more rapidly progressive course over weeks to months. SSPE can present with cognitive, epileptic, autonomic, pyramidal and ophthalmologic manifestations with scholastic decline being the primary feature. The management of SSPE focuses on improvement of quality of life and prolongation of survival which can be achieved with the use of supportive care modalities and immunomodulators respectively. This is a comprehensive review which discusses several parameters of SSPE such as epidemiology, pathophysiology, clinical presentations, and detailed management protocol for this condition. As part of this review, we also discuss a case of rapidly progressive, fulminant and atypical SSPE in a five-year-old male presenting clinically with myoclonic jerks of lower extremities.